Responding to Positive Emotions at Work – The Four Steps and Potential Benefits of a Validating Response to Coworkers’ Positive Experiences - Paakkanen, Miia A.; Martela, Frank; Pessi, Anne B. (Frontiers in Psychology, 2021)
In order to capitalize on positive emotions at work and build high-quality interpersonal relationships and psychological safety, it is important that coworkers respond to each other’s positive emotions in a constructive and validating way. However, despite the importance of symmetrical emotion regulation outcomes, organizational research has largely overlooked how an employee can positively respond to coworkers’ positive emotions. Existing research has concentrated almost exclusively on negative ways of responding, with a particular focus on envy. This article develops a theoretical model of employees’ positive responses to coworkers’ positive emotional experiences, introduced here as a validating response. We identify four steps – noticing, sensemaking, feeling, and acting – and the key mechanisms within each step that enable a responder to react in a validating way. We connect the validating response to important potential individual and organizational outcomes. These outcomes include improved relationship quality and trust, as well as increased positivity and well-being that can result in enhanced learning behavior and collaboration. This article also discusses the connection between a validating response and compassion. We identify them both as parallel affirmative processes that ackmowledge a coworker’s emotions, with the former being a response to positive emotion while the latter is a reponse to negative emotion.